ffect of wind induced to road accident at north-south expressway (Kuala Lumpur to Tangkak) - Siti Natrah , Musa (2012)
In becoming a develop country, Malaysia government had built infrastructure including highway for easy commute. Hence of that, North-South Expressway was built from Kuala Lumpur to Tangkak. This expressway was built through variation of roughness of Land Use Land Cover (LULC), terrain and topography. From this situation will make cross wind phenomena occurred along the road. Consequently, road accident could be happen due to the phenomena of cross wind. Therefore, in this study terrain database along North-South Expressway was established and relationship between slope topographic factor and wind speed was derived. Furthermore, access possibilities of the accident prone-location due to wind speed induced were identified. The GIS technique was used to establish database of study area and analysis information of topographic effect. The database demonstrate the system analyze in spatial analysis to obtain spatial variation of slope along that area. Indirectly, this technique has enabled GIS database showing the system analysis for the effect of topographic variation in slope was established. In conclusion, the objectives prove successful in the relation between data information and slope topographic effect of that area. Therefore, the result for this study can be made as a guideline for road construction and improvement in safety of the road users.